Association of IL-8 levels in serum and bronchoalveolar lavage fluid with sputum emboli in children with lobar pneumonia: Relationship between IL-8 and lobar pneumonia - Chen, Qingqing; Lv, Na; Wang, Xue; Liu, Lan; Lu, Yan (Cellular and Molecular Biology, 2023)
To provide a clinical reference for the management of lobar pneumonia (LP) by analyzing the association of interleukin-8 (IL-8) with the disease. A retrospective analysis was performed on 69 LP children (observation group, OG) and 60 healthy control children (control group, CG) who visited our hospital from January 2022 to November 2022. Fasting venous blood was drawn from the controls at admission to determine IL-8 levels. In addition, IL-8 concentrations in fasting venous blood and bronchoalveolar lavage fluid (BALF) were determined in LP patients in the observation group (OG) at admission and after treatment for comparative analysis with the control group (CG). The association of serum and BALF IL-8 levels in LP children, as well as the diagnostic value of IL-8 in LP, sputum emboli, and poor prognosis, were discussed.OG showed higher serum IL-8 levels than CG. Serum IL-8 had a diagnostic sensitivity of 80% and a specificity of 70% in diagnosing LP (P<0.05). Pearson correlation coefficients showed a positive correlation between IL-8 in serum and IL-8 in BALF in OG (P<0.05). In OG, IL-8 levels increased with LP progression and decreased after treatment (P<0.05). Similarly, IL-8 was increased in children with sputum emboli, and IL-8 in BALF was more effective in diagnosing sputum emboli formation (P<0.05). Finally, IL-8 also exhibited an excellent evaluation of poor prognosis in LP children after treatment (P<0.05).IL-8 is highly expressed in serum and BALF of LP children, which has excellent diagnostic effects on the occurrence of LP and the formation of sputum emboli.